2010
DOI: 10.1186/1476-7961-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-allergic rhinitis: a case report and review

Abstract: Rhinitis is characterized by rhinorrhea, sneezing, nasal congestion, nasal itch and/or postnasal drip. Often the first step in arriving at a diagnosis is to exclude or diagnose sensitivity to inhalant allergens. Non-allergic rhinitis (NAR) comprises multiple distinct conditions that may even co-exist with allergic rhinitis (AR). They may differ in their presentation and treatment. As well, the pathogenesis of NAR is not clearly elucidated and likely varied. There are many conditions that can have similar prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…Specifically, NAR covers a heterogeneous pattern of conditions which vary dramatically in their pathogenesis and need different treatments. A number of pathologies, including nasal polyposis, anatomical/mechanical factors, autoimmune diseases, immunodeficiency, metabolic and genetic conditions, induce a clinical scenario similar to that caused by NAR or AR, which sometimes makes their clinical diagnosis quite difficult . These conditions need to be accurately considered in the differential diagnosis, because therapies that are effective for AR (i.e., antihistamines and nasal corticosteroids) may be less effective for other types of rhinitis.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, NAR covers a heterogeneous pattern of conditions which vary dramatically in their pathogenesis and need different treatments. A number of pathologies, including nasal polyposis, anatomical/mechanical factors, autoimmune diseases, immunodeficiency, metabolic and genetic conditions, induce a clinical scenario similar to that caused by NAR or AR, which sometimes makes their clinical diagnosis quite difficult . These conditions need to be accurately considered in the differential diagnosis, because therapies that are effective for AR (i.e., antihistamines and nasal corticosteroids) may be less effective for other types of rhinitis.…”
Section: Introductionmentioning
confidence: 99%
“…При аллергическом рините больные жалуются на хроническую заложенность носа, зуд, насморк, пароксизмы чихания, иногда потерю восприятия запахов, храп, гиперемию и отечность конъюнктив [29,32]. Клинически фенотипы неаллергического ринита почти не отличаются от фенотипов аллергического [33]. Круглогодичный аллергический ринит обычно начинается в возрасте 3-5 лет.…”
Section: Aллергический ринит: фенотипы эндотипы и биологические маркерыunclassified
“…2,51,52 Regardless of whether any or all of these different endotypes are relevant, it is clear that eosinophilia contributes to direct mucosal damage, protracted mucociliary clearance, and nasal hyperresponsiveness. 50 Other studies have reported different inflammatory profiles in the nasal mucosa in patients with NAR, including mast cells and neutrophils, further complicating the utility of nasal histology as a biomarker for establishing reliable NAR endotypes. 53 In addition to NARES, at least 6 other clinical entities are included in the NAR classification: drug-induced rhinitis, gustatory rhinitis, hormone-induced rhinitis, atrophic rhinitis, rhinitis of the elderly, and IR ( Fig.…”
Section: Nonallergic Rhinitismentioning
confidence: 99%
“…The non-IgE-mediated immunologic-mediated endotype is primarily caused by low-molecular-weight agents, including reactive chemicals, transition metals, and wood dusts, and is less common. 50,102,103 Nonallergic occupational rhinitis, also termed reactive upper airways dysfunction syndrome, is caused by a single exposure to high chemical irritant concentrations or multiple exposures to lower chemical irritant concentrations over time, the latter form also being termed irritant-induced rhinitis. 50,104 Both of these subforms can lead to significant inflammatory and even structural damage, resulting in so-called corrosive rhinitis, which is the severe end-stage form of the irritantinduced endotype, and is most often caused by potent toxic irritants such as chlorine, sulfur dioxide, and ammonia.…”
Section: Occupational Rhinitismentioning
confidence: 99%